Helicobacter cinaedi Hepatic Cyst Infection with Bacteremia - Tetsuya Suzuki; Satoshi Kutsuna; Motoyuki Tsuboi; Masayuki Ota; Kayoko Hayakawa; Norio Ohmagari (Emerging Infectious Diseases, 2019)
Helicobacter cinaedi is an enterohepatic bacillus that causes infections of various manifestations. We report a novel case of hepatic cyst infection with bacteremia caused by H. cinaedi in an immunocompetent woman in Japan. Further research is warranted to identify the epidemiologic and clinical features of H. cinaedi infection.